1987
DOI: 10.1115/1.3248046
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Method for Heat Transfer During Film Condensation on Horizontal Low Integral-Fin Tubes

Abstract: A method for predicting the average heat transfer coefficient is presented for film condensation on horizontal low integral-fin tubes. Approximate equations based on the numerical analysis of surface tension drained condensate flow on the fin surface are developed for the heat transfer coefficients in the upper and lower portions of the flooding point below which the interfin space is flooded with condensate. For the unflooded region, the equation is modified to take account of the effect of gravity. These equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…6 it may be seen that, owing to line contact between the wire and tube there can be no "fin effect"; enhancement is solely due to surface tension. The mechanism of surface tension drainage is the same as that in the Honda et al (1987) (2) theory of condensation on integral fin tubes but no satisfactory theoretical solution or correlation has emerged to date for condensation on wire-wrapped tubes. The heat transfer depends on the geometric parameters (tube and wire diameter and pitch of winding) as well as vapour-to-surface temperature difference and fluid properties.…”
Section: Wire-wrapped Tubementioning
confidence: 85%
See 1 more Smart Citation
“…6 it may be seen that, owing to line contact between the wire and tube there can be no "fin effect"; enhancement is solely due to surface tension. The mechanism of surface tension drainage is the same as that in the Honda et al (1987) (2) theory of condensation on integral fin tubes but no satisfactory theoretical solution or correlation has emerged to date for condensation on wire-wrapped tubes. The heat transfer depends on the geometric parameters (tube and wire diameter and pitch of winding) as well as vapour-to-surface temperature difference and fluid properties.…”
Section: Wire-wrapped Tubementioning
confidence: 85%
“…A detailed theory of condensation on low-finned tubes was first developed by Honda and Nozu (1987) (2) and Honda et al (1988) (3) . The Nusselt approximations, together with the pressure gradient due to surface tension, results in a fourth order differential equation (Eq.…”
Section: Low Integral-finned Tubementioning
confidence: 99%
“…Honda and Nozu [55] provided a prediction method for heat transfer on horizontal trapezoidal integral-fin tubes. It was pointed out by the authors that an important factor, which had been ignored in earlier theoretical models, is the non-uniformity of wall temperature, due to the large difference in heat-transfer coefficients between the unflooded and flooded regions.…”
Section: The Model Ignored Condensation On the Fin Tipsmentioning
confidence: 99%
“…Honda and Nozu [55] compared their theoretical model with their own experimental data for the condensation of R-113 and methanol on three integral-fin tubes (see Honda et al [12]) and found agreement within ±10%. The same experimental data gave agreement with Beatty and Katz [49] model within ±20%.…”
mentioning
confidence: 98%
“…Kern [4] suggested using m=1/6 depending on a comparison with experiments [5]. In bundles of low-fin tubes, the condensation HTC can be calculated using analytical models [6][7][8][9]. These models take into account the tube geometry, surface tension effect, number of tubes in the bundle, and the condensate surface curvature.…”
Section: Introductionmentioning
confidence: 99%